Public Service Motivation and Socio Demographic Antecedents among Civil Service in Indonesia - Syamsir, Syamsir (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
Public Service Motivation (PSM) is still a nascent theory that need to be proved with any contexts of many countries around the world, especially developing countries that might have different contexts related to cultures, beliefs, views on the importance of financial rewards, etc. This study aims to identify the PSM level and socio-demographic antecedents, especially age, gender, marital status, education, income, and political ideology, among civil servants in Indonesia. Using mean and chi- square tests on responses by 398 respondents of civil servants in Padang, West Sumatra, this study tested the PSM levels and socio-demographic antecedents affecting the PSM level among the civil servants. The findings of this study indicated that the PSM level of the civil servants tends to be at a low level compared to that of civil servants in developed countries. In addition, there is significant correlation between some of socio demographic antecedents and the level of PSM. The results of this study imply that PSM theory is not cross-culturally viable.